Governamentalidade, biopolítica e biopoder: a produção identitária para o corpo velho nos discursos da mídia brasileira contemporânea - Monteiro, Maria Emmanuele Rodrigues (2014)
This thesis investigates media s discursive production about the "old body". The fact that the Brazilian elderly population has increased fivefold in the last thirty years, in quantitative and qualitative terms , aroused the interest of media institutions for elderly subjects due to increased goods and services consumption. Thus, we aimed to analyze the "old body" in Brazilian media, in order to explain how the knowledge-power relationship occurs in inclusion/ exclusion identities production that results in the spectacle of "superelder" / "gerontolescent" subject position, with the conducting wire Biopolitics , Biopower and Governmentality notions. We base our research on Discourse Analysis theoretical and methodological assumptions from Pêcheux with Michel Foucault s dialogues and Jean- Jacques Courtine s contributions for media wordings on old age, formatted in various genres - reportage, advertising and magazine covers , materialized in Época, Isto é and Veja magazines. Among the survey results, we found that the body, in the same way that idiom and language, is socially managed, working as producer of meanings matrix, supporting meanings. The " old body " thought from this cultural perspective, enables us to observe it from the symbolic transformations that body has undergone over time, within a collective memory, which is also changing , form the paradigms of each culture, expressing, thus, aspects of aging historically constituted.